AC to DC converter / Erwanas Asmar Ismail and Saiful Buhairie Mohamad Adnan - Ismail, Erwanas Asmar; Mohamad Adnan, Saiful Buhairie (2005)
An AC/DC converter is actually a rectifying circuit which converts an alternating current into a pulsating DC voltage which is a unidirectional current. A rectifier circuit allows currents to flow only in one direction. In other words, a rectifier is capable of converting a sinusoidal waveform (whose average value is zero), into a unidirectional waveform, whose average value is non-zero. There are two types of rectifiers, half-wave rectifier and full-wave rectifier. But to gain a much more improved DC level obtained from a sinusoidal input, AC/DC converter is very useful where its application has been used world wide. This is because of its capability of converting AC to DC, where most of sources that are being transmitted to users are in the form of AC. This is where the converter becomes an important tool to convert the AC to DC. This report will describe how the AC/DC converter is implemented in daily use and works by using the Circuit Maker program.